Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/mnras/staa1065
|View full text |Cite
|
Sign up to set email alerts
|

On the ejection of dark matter from globular clusters

Abstract: We propose a novel mechanism for the removal of a Dark Matter halo from a Globular Cluster: Through multi-body gravitational interactions, a Dark Matter particle can be accelerated above the escape speed of the cluster and be ejected. We find that this mechanism is not sufficient to eject a massive, extended Dark Matter halo by the present time. Combined with observations of isolated Globular Clusters that show no evidence of tidal stripping, these results suggest that Globular Clusters likely never possessed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…see Moore 1996;Saitoh et al 2006;Creasey et al 2019) and internal dynamical processes (e.g. see Bromm & Clarke 2002;Mashchenko & Sills 2005;Hurst & Zentner 2020) as well as feedback processes (Pontzen & Governato 2012; Davis et al 2014). It could be possible that some remnant of the DM halo is still preserved in the peripheries of present-day GCs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…see Moore 1996;Saitoh et al 2006;Creasey et al 2019) and internal dynamical processes (e.g. see Bromm & Clarke 2002;Mashchenko & Sills 2005;Hurst & Zentner 2020) as well as feedback processes (Pontzen & Governato 2012; Davis et al 2014). It could be possible that some remnant of the DM halo is still preserved in the peripheries of present-day GCs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, such over-dense DM cores in a globular cluster are quite speculative and not yet well established. It has in fact been shown that globular clusters do not have any DM over-densities [85][86][87][88]. Hence, the explanation of a sub-Chandrasekhar or O(1) M BH due to a PBH transit hinges on the contentious assumption of a high DM density in globular clusters, and remains uncertain until the provenance of globular clusters is settled.…”
Section: Excluded From Existence Of Psr J0437-4715mentioning
confidence: 99%